Colombia-Peru FTA and regional integration in Latin America: Towards an “Americanization” of the European interregional strategy? - Parra, Andrea (2012)
This document compares the contents of the Free Trade Agreements (FTA) that have been signed by the European Union and the United States with Colombia. It analyses them from a perspective that characterizes FTAs into “WTO-extra” and “WTO-plus” agreements. With this analysis, an “Americanization” of the European interregional strategy is partially verified. Nevertheless, this “Americanization” appears to be partial, due to the inclusion of “regional integration” as a transversal theme in European FTA.